A meta‐analysis of infants' word‐form recognition. (23rd February 2021) - Carbajal, Maria Julia; Peperkamp, Sharon; Tsuji, Sho
Abstract: Recognizing word forms is an important step on infants' way toward mastering their native language. The present study takes a meta‐analytic approach to assess overarching questions on the literature of early word‐form recognition. Specifically, we investigated the extent to which there is cross‐linguistic evidence for an early recognition lexicon, and how it may be influenced by infant age, language background, and familiarity of the selected stimuli (approximated by parent‐reported word knowledge). Our meta‐analysis—with open data access on metalab.stanford.edu—was based on 32 experiments in 16 different published or unpublished studies on infants 5–15 months of age. We found an overall significant effect of word‐form familiarity on infants' responses. This effect increased with age and was higher for infants learning Romance languages than other languages. We further found that younger, but not older, infants showed higher effect sizes for more familiar word lists. These insights should help researchers plan future studies on word‐form recognition.